A Systematic Literature Review (SLR) on benefits of biophilic design strategies towards occupants’ perceived psychological performance in Malaysia office building / Sitinur Kamilah Mohd Idris, Asniza Hamimi Abdul Tharim and Azman Zainonabidin - Mohd Idris, Sitinur Kamilah; Abdul Tharim, Asniza Hamimi; Zainonabidin, Azman (2021)
Construction in Malaysia has been growing rapidly and constantly developing. This promotes economic growth resulting in the increase of goods prices, and competition for occupation. Thus, this requires occupants to work diligently resulting in them to spend most of their time working indoors. Due to the circumstances, occupants need to work longer hours to fulfill the expectation of the employers such as to meet the deadline and perform task requirements. Focussing on their work nonstop can develop different types of health issues such as stress, unstable emotions, and unproductive well-beingThus, this can bring degradation of occupants’ psychology. Maintaining individuals’ personal psychology is very crucial to enhance their work performance. One of the ways to do so is by being closer to natures. However, the nature of their work limits their interaction with natural environments. This is where Biophilic design comes to rescue. Previous studies show that nature can help in enhancing human wellbeing and psychology. Biophilic design is a strategy to connect humans with nature into the built environment such as the application of greens, natural light and ventilation, and elements of water. There are massive benefits of biophilic design, yet there is lack of awareness and knowledge towards biophilic design in Malaysia. Hence, this paper will highlight the benefits of biophilic design strategies towards occupants’ perceived psychological performance by using a Systematic Literature Review (SLR). It is hoped that the outcome of the paper will contribute to the understanding and importance of biophilic design strategies towards occupants’ psychology and well-being.